Education privatisation policy reforms in Tanzania and New Zealand since the 1980s : a comparative critical policy analysis study : a thesis presented in partial fulfilment of the requirements of the degree of Doctor of Philosophy in Education, Massey University, Palmerston North, New Zealand - Muganda, Cornelia Koku (Massey University, 1999)
This thesis is a comparative study of contemporary education policy reforms in Tanzania and New Zealand. It explains why and how Tanzania and New Zealand introduced and implemented education privatisation policy reforms in the 1980s and 1990s. The study analyses the socio-economic and discursive influences on national education policies and discusses the implications of current market-oriented education policies for the state's provision of education and for social justice in education. Employing comparative education policy analysis (CEPA) approach, the thesis traces the genesis of contemporary education privatisation policy reforms in Tanzania and New Zealand within the contexts of wider transformations in the capitalist world system. It is argued, in the study, that national education policies have been changing according to the nature, functions and position of the state within the capitalist formation. The thesis also underscores the critical importance of analysing policy documents. The researcher argues that the analysis of the education policy documents enables the policy analyst to deconstruct the policy discourse and reveal the policy implications to various groups of people in the society. Through critical discourse analysis, (CDA) this study explicates how the discourse of privatisation supports and legitimates the development and implementation of market oriented education policies in Tanzania and New Zealand. The thesis further argues that the market panacea espoused in current education privatisation policy reforms has adverse implications for social justice in education and for the state provision of education, particularly in relation to "children at risk". Finally the thesis proffers suggestions for alternative policy interventions and identifies some of the areas that need further research.
Keywords: Education and state; Privatisation; Government policy; New Zealand; Tanzania; Comparative education policy